Pengaruh Kompensasi terhadap Kepuasan Kerja Pegawai Bagian SDM & Umum PT KAI Daerah Operasi 1 Jakarta - Rahayu, Gappuraning; Pramularso, Eigis Yani (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Abstract  –  Compensation is one of the important parts in an effort to meet job satisfaction for employees in an organization. With high job satisfaction employees are expected to feel happy at work, more motivated in work, increased productivity, and make employees become more loyal to the organization. This study aims to determine the effect of compensation on employee job satisfaction at PT Kereta Api Indonesia (Persero) Operational Area 1 Jakarta. The study was conducted by dividing the questionnaire to a number of 35 people, all employees of the general section and HR who were used as research samples. Data analysis using simple regression analysis, correlation coefficient, and coefficient of determination. The results of the study indicate a positive and direct effect between compensation for employee job satisfaction. Based on the calculation of the correlation coefficient obtained a result of 0.723 where the number of scores shows the strong relationship of compensation to employee job satisfaction. From the calculation of the coefficient of determination, it can be seen that compensation affects employee job satisfaction by 52.3% while the remaining 47.7% is influenced by other factors beyond research. Key Word: Financial compensation, non financial compensation,  Job Satisfaction